2024
DOI: 10.1186/s12931-024-02732-2
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin for reduction of 28-day mortality in severe and critical COVID-19 patients: a randomized controlled trial

Naglaa Hamdi Eltahan,
Neamat Hamdy Elsawy,
Kholoud M. Abdelaaty
et al.

Abstract: Background COVID-19 is an abnormal host response to the SARS-CoV-2 infection, which is associated with endothelial dysfunction and multi-organ failure. Atorvastatin has been proposed to reduce COVID-19 severity and mortality in chronic and de-novo users. Methods This randomized double-blind trial included 220 COVID-19 patients admitted to Mansoura University's isolation hospital in Egypt. One hundred and ten cases were given 40 mg of atorvastatin o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…It has been postulated that a protective effect of statins may result from their anti-inflammatory effects, possibly via decreasing lipid particle clearance of lipogenic viral particles whose clearance is slowed and half-life prolonged, and/or a direct inhibitory effect on SARS-CoV-2 infectivity ( 39 , 40 ). However, a meta-analysis of randomized controlled trials observed no benefit in adding statins to COVID-19 treatment ( 41 ), a finding further supported by recently published studies ( 42 , 43 ). In a small study, the use of proprotein convertase subtilisin/kexin type 9 inhibitors was shown to increase survival for 30 patients with COVID-19; however, additional larger studies are required to confirm this finding ( 44 ).…”
Section: Discussionmentioning
confidence: 54%
“…It has been postulated that a protective effect of statins may result from their anti-inflammatory effects, possibly via decreasing lipid particle clearance of lipogenic viral particles whose clearance is slowed and half-life prolonged, and/or a direct inhibitory effect on SARS-CoV-2 infectivity ( 39 , 40 ). However, a meta-analysis of randomized controlled trials observed no benefit in adding statins to COVID-19 treatment ( 41 ), a finding further supported by recently published studies ( 42 , 43 ). In a small study, the use of proprotein convertase subtilisin/kexin type 9 inhibitors was shown to increase survival for 30 patients with COVID-19; however, additional larger studies are required to confirm this finding ( 44 ).…”
Section: Discussionmentioning
confidence: 54%